Crystal structure of benzylthiouronium chloride, C8H11ClN2S - Maritz Marius; Hosten Eric C.; Betz Richard (Zeitschrift für Kristallographie - New Crystal Structures, 2021)
C8H11ClN2S, orthorhombic, Pbca (no. 61), a = 11.3126(6) Å, b = 8.3567(4) Å, c = 20.4130(11) Å, V = 1929.76(17) Å3, Z = 8, Rgt(F) = 0.0240, wRref(F2) = 0.0680, T = 200 K.